(untitled) (World Economics and Finance Bulletin, 2024)
Modern information technologies play an effective and positive role in improving administrative and financial work, especially in the field of scientific research in Iraqi universities. It has become necessary to keep pace with the rapid progress and development in information technologies by providing and using equipment, devices, and other means of communication. It carefully and scientifically stores information, processes it, retrieves it as quickly and cheaply as possible, and presents it to its users in a timely manner, as traditional methods have been unable to provide the required data and information in a timely manner.